2007
DOI: 10.1111/j.1745-6916.2007.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychology as the Science of Self-Reports and Finger Movements: Whatever Happened to Actual Behavior?

Abstract: Psychology calls itself the science of behavior, and the American Psychological Association's current "Decade of Behavior" was intended to increase awareness and appreciation of this aspect of the science. Yet some psychological subdisciplines have never directly studied behavior, and studies on behavior are dwindling rapidly in other subdisciplines. We discuss the eclipse of behavior in personality and social psychology, in which direct observation of behavior has been increasingly supplanted by introspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
1,047
2
17

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,383 publications
(1,085 citation statements)
references
References 34 publications
(37 reference statements)
19
1,047
2
17
Order By: Relevance
“…Research on MI shows that self-reported communication skills share minimal variance with actual verbal behaviour when sampled from an interaction (Miller et al, 2004). Yet, research based on real behavioural observations remains scarce (Baumeister et al, 2007). Addressing this concern, our findings show that resistance to change can be measured on the basis of behavioural observations.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Research on MI shows that self-reported communication skills share minimal variance with actual verbal behaviour when sampled from an interaction (Miller et al, 2004). Yet, research based on real behavioural observations remains scarce (Baumeister et al, 2007). Addressing this concern, our findings show that resistance to change can be measured on the basis of behavioural observations.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
“…Self-reports of inner states are not necessarily accurate in predicting hypothetical future behaviour (Back & Egloff, 2009;Baumeister, Vohs, & Funder, 2007;Miller, Yahne, Moyers, Martinez, & Pirritano, 2004;Mischel, 1968). Research on MI shows that self-reported communication skills share minimal variance with actual verbal behaviour when sampled from an interaction (Miller et al, 2004).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Contrary to our predictions, however, primed anxiety, although affecting condom use attitudes (in Studies 1 and 2), did not appear to have an effect on condom acquisition behavior. Although this null effect was surprising, it helps to highlight the need for scholars to consider the use of behavioral measures of the sexuality-related phenomena they study, because in some circumstances-as in the case of the present study-psychological effects on attitudes and self-reports of behavior may not always neatly transfer over to behavioral indicators (Baumeister et al, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…We therefore conducted the first examination of the effects of experimentally primed attachment on an observational measure related to condom use (Baumeister et al, 2007): condom acquisition behavior. Based on our previous findings, we predicted that participants primed with attachment security or anxiety would take fewer condoms compared to participants in other conditions.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation